"Khorchin" embroidery result was experimented with in fine arts and local courses - Jin Fu; Ariunjargal Lkhagva (Lavai, 2024)
Protecting and inheriting the culture of small nations with the development of technology and globalization is an important issue. One that takes up a lot of operational resources is the legacy of educational programs and content tools. The article reflects the results of a study on the possibility of implementing khorchin embroidery, one of the traditional cultures of the khorchin people living in the eastern part of China, in teaching secondary education schools. To achieve this goal, we analyzed government documents on traditional culture and educational content related to traditional culture. Based on these results, the organization of pilot lessons in elementary visual arts and local subjects. Also, the student’s knowledge and understanding of needlepoint embroidery were discovered. Based on that, an experimental lesson program was developed, the practical lesson was organized in stages, and the results were calculated. As a result of the research, it was revealed that the pilot lesson was successful and effective because the students tended to respect the characteristics, symbols, patterns, usage, and traditional culture of embroidery. In order to calculate the results, 3 surveys were conducted from the students and in-depth-interview with the teachers were held. As a result of the experimental lesson, the students learned that the traditional culture of khorchin is khorchin embroidery. Also, the students are familiar with the basic concepts such as patterns, colors, basic methods, and symbols of embroidery.